Effect of the anxiolytic fabomotizol on the time parameters of atrial depolarization in the acute phase of myocardial infarction - S. L. Smirnova; I. M. Roshchevskaya; I. B. Tsorin; S. A. Kryzhanovskii (LLC "Publisher OKI", 2023)
The aim of the work is to study the effect of the anxiolytic fabomotizole (15 mg/kg, i.v.) on atrial depolarization in the acute phase of myocardial infarction using the method of synchronous multichannel cardioelectrochronotopography. Synchronous multichannel cardioelectrochronotopography was used to study the sequence of depolarization of the atrial epicardium in outbred rats during the acute phase of myocardial infarction caused by ligation of the anterior branch of the left coronary artery with simultaneous administration of the σ1-receptor agonist fabomotizole. Significant differences in the temporal characteristics of atrial depolarization in the acute phase of myocardial infarction were revealed in control animals and animals treated with fabomotizol. In rats against the background of fabomotizol, changes in the time of the onset of epicardial depolarization, the transition of the excitation wave from the right to the left atrium, and the end of depolarization, compared with the initial state, occur by the 5th minute after the ligation of the coronary vessel; in the process of further development of acute myocardial infarction, changes in time parameters are not observed .In animals of the control group, changes in the time parameters of atrial depolarization after coronary vessel ligation develop by 10 minutes after ligation and continue to change as acute myocardial infarction develops. Anxiolytic fabomotizol in the most acute phase of myocardial infarction changes the time parameters of atrial depolarization, preventing the development of atrial fibrillation.